False Node Recovery Algorithm for a Wireless Sensor Network - Rajesh J; D. Venkata Subramanian (Institute of Advanced Engineering and Science, 2015)
This paper proposes a fault node recovery algorithm to enhance the lifetime of a wireless sensor network when some of the sensor nodes shut down. The algorithm is based on the grade diffusion algorithm combined with the genetic algorithm. The algorithm can result in fewer replacements of sensor nodes and more reused routing paths. In our simulation, the proposed algorithm increases the number of active nodes up to 8.7 times, reduces 98.8%, and reduces the rate of energy consumption by approximately 31.1%. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6995